Working with people outside the limelight - Lazarus, Ray (PINS-Psychology in Society, 2026)
Book review Lea, S & Foster, D (eds) (1990) Perspectives on mental handicap in South Africa. Durban: Butterworths, ISBN 0 409 10919 3. Estimates of prevalence suggest that there are 150 000 - 250 000 South Africans with moderate or severe mental handicap. A further 1 million or so might be described as mildly mentally handicapped. Each of these people is linked with a family and community which also has to come to terms with the social, emotional, physical and financial implications of mental handicap. If only because of the numbers of people involved, mental handicap must thus be seen as a major mental health issue in South Africa. The inequity/iniquity in the treatment of people with mental handicap, especially those not classified white, should also surely be of concern to progressive mental health workers. Yet, despite the upsurge of involvement in social issues during the eighties, for most mental health workers, mental handicap has remained invisible. A book devoted to the topic and written from a progressive perspective is therefore long overdue.